Quantitative analysis of therapeutic response in psoriatic arthritis of digital joints with Dual-energy CT iodine maps - Kayama, Reina (Sci Rep, 2020)
The aim of this study was to investigate the feasibility of quantitative assessment of the therapeutic response in psoriatic arthritis (PsA) by measuring iodine uptake using a Dual-energy CT (DECT) iodine map. The study included 74 symptomatic and 74 matching non-symptomatic joints of 26 consecutive PsA patients who underwent two contrast enhanced DECTs of the hand or foot, pre and post medical interventions. Symptomatic and matched non-symptomatic control joints were scored with the PsA DECT Scoring System (PsADECTS), which was derived by modifying the PsA MRI Scoring System (PsAMRIS), a recently validated scoring system that assesses PsA changes on MRI. Quantified iodine uptake measured using the DECT iodine map was compared to the PsADECTS score. Efficacy of PsA treatment was confirmed by the improved clinical findings. Both PsADECTS and iodine uptake also showed significant improvement after treatment (Wilcoxon signed-rank test: z = 7.38, p < 0.005; z = 6.20, p < 0.005, respectively). The treatment effects of PsADECTS score and iodine uptake showed a good correlation with each other (Spearman’s ρ = 0.58 p < 0.005). Inter-reader agreement for PsADECTS score and iodine uptake were either moderate or good. In conclusion, our study showed that the DECT iodine map is a valid tool for quantitative assessment of the therapeutic response of PsA.